Literature Review Study: Learning Model for Indonesian Language Lectures - Yani, Ahmad (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research seeks to explore different learning models employed in Indonesian language classes via a literature review. The approach entails performing a structured search of the Google Scholar database utilizing terms like